2011
DOI: 10.1590/s1517-83822011000200021
|View full text |Cite
|
Sign up to set email alerts
|

Quality of water sources used as drinking water in a Brazilian peri-urban area

Abstract: The objective of this paper was to assess bacteriological quality of drinking water in a peri-urban area located in the Metropolitan Region of São Paulo, Brazil. A total of 89 water samples were collected from community plastic tanks and 177 water samples from wells were collected bimonthly, from September 2007 to November 2008, for evaluating bacteriological parameters including: Escherichia coli, Enterococcus and heterotrophic plate count (HPC). Clostridium perfringens was investigated in a subsample (40 sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…Assessment of water samples in plastic tanks and in wells (89 and 177) in an area within the metropolitan region of São Paulo, Brazil, revealed that enterococcus microorganisms were extant in 21 samples (23.5%) for plastic tanks and in 142 samples (80.2%) for wells, enhancing possible interventions due to fecal contamination (Razzolini et al, 2011).…”
Section: Microbiological Assessmentmentioning
confidence: 99%
“…Assessment of water samples in plastic tanks and in wells (89 and 177) in an area within the metropolitan region of São Paulo, Brazil, revealed that enterococcus microorganisms were extant in 21 samples (23.5%) for plastic tanks and in 142 samples (80.2%) for wells, enhancing possible interventions due to fecal contamination (Razzolini et al, 2011).…”
Section: Microbiological Assessmentmentioning
confidence: 99%
“…É crescente o número de surtos infecciosos transmitidos por via hídrica e de estudos reportando a presença ou traços de contaminantes e patógenos, dentre bactérias, vírus entéricos e protozoários, em águas subterrâneas urbanas e rurais. Na literatura são relatadas contaminações bacterianas por E. coli, Clostridium perfringens e Enterococcus; virais por adenovírus (AdV), enterovírus (EV), rotavírus (RV), vírus da hepatite A, norovírus, e echovírus; além de protozoários e contaminação por uso de pesticidas ou resíduos industriais (De Serres et al, 1999;Fout et al, 2003;Borchardt et al, 2007;Naik et al, 2007;Ribeiro et al, 2007;Colvara et al, 2009;Ogorzaly et al, 2010;Razzolini et al, 2011a;2011b). O consumo da água contaminada pode causar desde doenças entéricas e hepatites, até o óbito (Schijven et al, 2010;Lenaerts et al, 2008).…”
Section: Introductionunclassified
“…Como exemplo da interface entre o domínio publico e o domiciliar, o estudo realizado em área periurbana da região metropolitana de São Paulo aponta melhores indicadores de qualidade da água para consumo humano em componente público (tanques coletivos) em relação às alternativas domiciliares (poços domiciliares) (RAZZOLINI et al, 2011). No entanto, a porcentagem das amostras nos tanques coletivos em desacordo com os padrões brasileiros de potabilidade para consumo humano poderia atingir números ainda menores com intervenções educativas relacionadas a hábitos de higiene e manutenção dos tanques.…”
Section: Schistosomose Malária Dengueunclassified